2005
DOI: 10.1002/ijc.21461
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the PI3K‐AKT pathway in uterine cervical neoplasia: Frequent PIK3CA amplification and AKT phosphorylation

Abstract: Uterine cervical carcinogenesis is probably dependent on cellular genetic damage in addition to the integration of high-risk HPV DNA in the epithelial cell genome. Gain of chromosome 3q24-29 is commonly observed in cervical neoplasia. The putative oncogene PIK3CA located in this region encodes a phosphatidylinositol 3-kinase (PI3K). In a process reversed by PTEN, PI3K generates inositol phospholipids that trigger AKT phosphorylation, which in turn effects tumor driving signals. We studied 46 specimens of forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
3
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 50 publications
3
105
3
2
Order By: Relevance
“…In our study, no relation between loss of PTEN and activation of the AKT pathway was found. Our low percentage (5.3%) of pAKT-positive cases is in contrast to previous studies in cervical cancer that used the same antibody and staining protocol but observed 29% to 94% pAKT-positive cases [22][23][24]. A major difference between these studies and our study is that we assessed pAKT in a much larges series (310 vs 31) of earlystage cervical cancer patients.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…In our study, no relation between loss of PTEN and activation of the AKT pathway was found. Our low percentage (5.3%) of pAKT-positive cases is in contrast to previous studies in cervical cancer that used the same antibody and staining protocol but observed 29% to 94% pAKT-positive cases [22][23][24]. A major difference between these studies and our study is that we assessed pAKT in a much larges series (310 vs 31) of earlystage cervical cancer patients.…”
Section: Discussioncontrasting
confidence: 88%
“…Loss of PTEN can be due to mutations, deletions, gene promoter methylation, or microRNAs (miRs) [25][26][27][28]. Mutations and deletions of PTEN are rare events in cervical cancer [16,22,29]. In a study by Yang et al, PTEN methylation was observed in 20 (15.7%) of 127 cervical cancers, whereas Cheung et al [16] reported PTEN methylation in 36 (58%) of 62 of squamous cell cervical cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also found that amplification of the PIK3CA gene accompanied by serine 473 phosphorylation of AKT is common in cervical cancers and it seems to be an independent event to HPV infection (Ma et al, 2000;Zhang et al, 2002;Bertelsen et al, 2006). Under our current condition, only 9.8% of cervical cancers and 6.2% of esophageal cancers were pAkt positive.…”
Section: Discussionmentioning
confidence: 95%
“…Akt is equally attractive as mTOR for molecular targeting in therapeutics due to its participation in important cellular functions, including cell cycle progression, gene transcription and translation, apoptosis and cellular metabolism. Bertelsen et al (43) observed that in cervical carcinogenesis there was an increased activation of Akt due to PI3KCA gene amplification, raising the intracellular levels of PI3K. The mechanism of Akt activation by amplification of PIK3CA was also demonstrated in anal squamous cell carcinoma.…”
Section: Intracellular Signaling Kinasesmentioning
confidence: 95%